Understanding science teachers’ TPACK for virtual lab adoption in rural schools in South Africa: a mixed-methods approach - Shambare, Brian; Jita, Thuthukile (Frontiers in Education, 2024)
This paper reports on a sequential explanatory mixed-methods study that assessed technological, pedagogical and content knowledge (TPACK) competency among life sciences teachers in the context of virtual lab adoption in rural schools in South Africa. Drawing from Koehler and Mishra's (2006) TPACK framework as the study's theoretical foundation, data gathered through questionnaires (N = 186) and in-depth semi-structured interviews (N = 4) were analysed using descriptive and thematic analysis. The study uncovered a ubiquitous deficiency in TPACK competency among the participating life sciences teachers. The teachers demonstrated significant expertise in conventional areas such as content knowledge (CK), pedagogical knowledge (PK), and pedagogical content knowledge (PCK), mainly influenced by teaching experience. However, they exhibited a noticeable gap in technology-related TPACK domains, including technological knowledge (TK), technological pedagogical knowledge (TPK), and overall TPACK proficiency.This paper aspires to address a significant gap in educational research by spotlighting the oftenoverlooked rural teaching contexts. In addition, the paper advocates for tailored professional development initiatives to enhance teachers' overall TPACK proficiency. Such initiatives are crucial for empowering teachers to integrate technology into their teaching and improve learning outcomes effectively.